Differences in Quality of Life of Stunting Children based on Caries Status in Indonesia - Husain Akbar, Fuad; Pratwi, Rini; Hulwah, Nadiah (Brazilian Dental Science, 2020)
Objective: The aim of this study was to determine the difference in quality of life of stunting children in Enrekang District based on their caries status. Material and Methods: This study was an observational analitic study with a cross sectional design, conducted in Buntu Batu, Baraka, and Malua Sub-district of Enrekang District on April 29-May 3, 2019. Height measurements, def-t/DMF-T, pufa/PUFA  assessment of stunting children 6-12 years old, and assessment of quality of life related to oral health of children 8-12 years using the CPQ questionnaire. Data were collected, 123 children suffered from stunting. Results: Based on the Mann Whitney Test, p value  < 0.05 showed that there were differences that statistically significant on def-t and pufa to quality of life of 8-10 years. The p value > 0.05 indicates that there are no significant differences in def-t/DMF-T and pufa/PUFA to quality of life of 11-12 years stunting children. Conclusion: There are differences in caries of primary teeth between stunting children aged 8 -10 years to their quality of life. At the age of 11-12 years there is no difference in caries to quality of life in Enrekang District.KeywordsCaries; Quality of life; Stunting.